Brane (-Antibrane) Inflation - Năstase, Horaţiu [UNESP] (My University, 2019)
In this chapter we will examine the possibility that we have inflation due to branes, or perhaps a brane-antibrane system. In string theory, we have branes as we saw, in particular Dp-branes. They move in a higher dimensional space (usually 10 dimensions), and then from the point of view of their worldvolume, the positions in the extra dimensions behave as scalars. If moreover we adopt a point of view that our 3+1 dimensional world lives on the worldvolume of these branes (a scenario known as “braneworld”), then the extra dimensions are 3+1 dimensional scalars. It is therefore natural to ask whether one of them, X(ξa), can be the inflaton.